Editorial - Fernando, Maria Socorro C.L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The Editorial Team presents the 2nd issue of Volume 12 of the ABAC ODI Journal Vision. Action. Outcome. This issue has 18 articles from authors who shared knowledge on valuable and quality topics and processes. The articles used various research designs such as quantitative research, mixed method and qualitative research, and action research on topics related to organization development and management, hotel and tourism management, educational leadership and management, technology and teaching processes, technology education management, change management and sustainability of teams and organizations. The studies represent a myriad of organizational contexts from several countries. It is our hope that the published articles will contribute valuable new knowledge in terms of innovative insights and applied learning experiences. We appreciate the authors who have published the journal. We also extend our gratitude to the Editorial Advisory Board, Editorial Board, and the Editorial Team together with all our experts who serve as peer reviewers for their continuous support and engagement in ensuring that this journal continues to develop as an international knowledge sharing hub of scholarly contributions of researchers on academic information ,inquiry , research , updates and best practices in the multi-disciplinary field organization development, management , leadership and related social and human sciences. Furthermore, the journal will have three issues per year starting April 2025. Issues will be January to April, May to August , September to December.